The status of women in Maldives : with special reference to the Family Law Act 2001 - Nafiz, Minnaa (Ahmad Ibrahim Kulliyyah of Laws, International Islamic University Malaysia, 2007)
The development of any country can be judged by the position and status enjoyed by women. This is because women are part and parcel of each and every society. However, from time immemorial women has been constantly subordinated by men. Their rights suppressed and sometimes even their very existence seems to be insignificant. This is the hard fact reality which exists through out the world and Maldives is no exception. It is with regret to note that their presence remains under the shadow of the ever looming presence of the males. Submerged under the dominancy of males, their due rights bestowed by Islam seem to occupy a secondary position. This fact is most obvious in the arena of their matrimonial life. Maldivian women used to be in the constant fear of arbitral divorce by their husbands, the never ending struggles of maintenance amidst the burden of managing the housework and the rearing of children without any support of their husbands. It was against this back ground of bitter reality, the Family Act came into existence in July, 2001. The emergence of this Act lifted the hopes and spirits of many women. Their hopes of freedom to contract marriages without compulsions, hopes of protection against rash and impulsive divorce and hopes of improving their maintenance rights. Therefore, five years after the Act, it is important to determine how far the Act has been successful in fulfilling these dreams of the women. Therefore, this research explores these issues and in doing so has adopted a comparative descriptive method, based mainly on the available literature related to the study and the various legislations from different countries. Due to the absence of research conducted on women's rights in Maldives, it is hoped that this study will contribute to promote their rights with a view towards suggesting legal reforms of the Act and policy recommendations relating to the matrimonial laws of the country.